Toward a Feminist Theory of Disability - Wendell, Susan (Hypatia, 1989)
We need a feminist theory of disability, both because 16 percent of women are disabled, and because the oppression of disabled people is closely linked to the cultural oppression of the body. Disability is not a biological given; like gender, it is socially constructed from biologically reality. Our culture idealizes the body and demands that we control it. Thus, although most people will be disabled at some time in their lives, the disabled are made "the other," who symbolize failure of control and the threat of pain, limitation, dependency, and death. If disabled people and their knowledge were fully integrated into society, everyone's relation to her/his real body would be liberated.
Keywords: 1900-1999; 1980-1989; EDI; approches et analyses; bioéthique; care; corps; cours; discipline; intersectionnalité; philosophie; premier cycle; périodes historiques; ressource en ligne; santé; sciences humaines; sex1911; sex1920; thématiques; éthique; études critiques du handicap

La dialectique de la reproduction - O'Brien, Mary (Les éditions du remue-ménage, 1987)
Dans La dialectique de la reproduction, essai de philosophie féministe, Mary O’Brien montre comment la pensée masculine et les institutions patriarcales ont été édifiées pour contrecarrer l’incertitude de la paternité et pour médiatiser l’exclusion des hommes du travail reproductif.
Keywords: 1900-1999; EDI; approches et analyses; care; corps; cours; discipline; division sexuelle du travail; fem1000; justice reproductive; philosophie; premier cycle; périodes historiques; sciences humaines; thématiques; travail du care

Repères dans l’évolution d’une épistémologie féministe - Lasvergnas, Isabelle (Des femmes dans les sciences, 1986)
Un témoignage de quelques unes des formes des interrogations théoriques féministes telles qu'elles se sont structurées au cours des trente dernières années, et telles qu'elles prolifèrent désormais dans la polysémie — ainsi se présente ce numéro spécial des Cahiers de Recherche sociologique sur la thématique «Des femmes dans les sciences et des sciences sur les femmes».
Keywords: 1900-1999; EDI; approches et analyses; cours; discipline; discours dominant; fem1000; inégalités; premier cycle; périodes historiques; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; épistémologie

Black women: Shaping feminist theory - hooks, bell (Feminist theory: From margin to center, 1984)
Keywords: 1900-1999; EDI; amériques; approches et analyses; cours; fem1000; intersectionnalité; justice sociale; militance; premier cycle; périodes historiques; ressource en ligne; régions géographiques; thématiques; états-unis